3D Technologies as the Future of Spatial Planning: the Example of Krakow - Bieda, Agnieszka; Bydłosz, Jarosław; Parzych, Piotr; Pukanská, Katarína; Wójciak, Ewelina (Geomatics and Environmental Engineering, 2020)
The main goal of the paper is to make a general assessment of the application of 3D technologies in spatial planning. It was performed with the city of Krakow as the case study. The paper describes the outline of the spatial planning system in Poland and the planning conditions of Krakow. The data obtained from laser scanning for Krakow are also briefly characterized. The possibility of using these data for locating high-rise buildings in terms of the protection of Krakow´s panorama and within two programs "œIT system of the Country´s Protection Against Extreme Hazards" (ISOK) and "œIntegrated spatial data monitoring system for air quality improvement in Krakow" (MONIT-AIR) were analyzed in the paper. The main result of the research is the assessment of what studies or measurements may be used to meet particular spatial planning needs or requirements.